Case Study: A Depiction of Blood Pressure Following Hatha Yoga Practice - Munawarah, Siti; Segita, Riri (PT. Riset Press International, 2023)
Hatha Yoga, characterized by body posture formation techniques and controlled breathing exercises, seeks to maintain the body's natural equilibrium. Conversely, hypertension, marked by elevated blood pressure within the vascular system, is a persistent medical condition. Its prevalence increases with age, particularly in low and middle-income nations. This study explores the effect of Hatha Yoga exercises on blood pressure in elderly hypertensive patients at the Biaro Public Health Center in 2023. Employing a Quasi-Experimental One Group Pretest-Posttest Design, this research engaged a study population comprising individuals aged 45-59 years. Purposive sampling identified a sample of 12 participants. Over a 2-week period, data was collected utilizing an aneroid sphygmomanometer and observation sheets. Data analysis encompassed univariate and bivariate analyses, employing the paired t-test. The results revealed that the mean blood pressure in hypertensive patients prior to participating in Hatha Yoga was 155.50, whereas following the intervention, it reduced to 150.08. These outcomes indicated a substantial impact, as evidenced by a p-value of 0.030, surpassing the significance level α (0.05). In conclusion, Hatha Yoga exercises significantly influenced blood pressure in elderly hypertensive patients at the Biaro Public Health Center in 2023. Consequently, it is recommended that hypertensive elderly individuals incorporate regular and disciplined Hatha Yoga exercises into their routine to effectively manage their blood pressure.